Faunistic survey of Hydromedusae (Cnidaria, Medusozoa) from the coast of Paraná State, Southern Brazil - Nagata, Renato Mitsuo; Júnior, Miodeli Nogueira; Haddad, Maria Angélica (Zootaxa, 2014)
This study is the first faunistic inventory of hydromedusae from the inner continental shelf of Paraná State. We describe the composition of hydromedusae species, collected with bottom-trawl and Hensen nets, in campaigns carried out from 1997 to 2006. We analyzed 17,797 specimens from 578 samples, and provide descriptions, photographs, and information about the biology of the 22 species found. All species had previous records from the Brazilian coast; however, this is the first record of Bougainvillia frondosa, Ectopleura dumortieri, Cirrholovenia tetranema, Eucheilota maculata, Gossea brachymera, Solmaris corona, and Amphogona apsteini for the coast of Paraná. Most species are typical of tropical and subtropical coastal waters from the South Brazilian Bight. However, Turritopsis nutricula, Niobia dendrotentaculata, Solmaris corona, and Aglaura hemistoma are abundant in oceanic waters, and Olindias sambaquiensis and Solmaris corona are associated with colder waters (<20°C). The current number of species known for the state is 26. Additional collection effort is needed in regions not sampled in this work, such as bays and offshore waters.